Advanced electrodes for hybrid electrochemical capacitors - Rohit Satish (2017)
The aim of this thesis is to study a new kind of energy storage solution known as “Hybrid Electrochemical capacitor” which allows for the integration of two existing technologies Lithium ion batteries and supercapacitors. The resulting device has the promising properties of both these devices, and can further be fine-tuned to meet the demands of autonomous industry vehicles and Plug-in Hybrid Electric Vehicles. The thesis achieves the above aim by the development and study of electrode materials that can meet the requirements of hybrid electrochemical capacitors. Initial studies are based on the narrowing down of appropriate intercalation materials which can be used as electrodes for a hybrid capacitor. This is achieved in three steps. A benchmark is set using a high Lithium ion conducting type electrode followed by fundamental understanding of the effect of electrode polarity on the energy density of hybrid capacitors. A working prototype cell is constructed using the above rule. Further improvements on the hybrid capacitor are planned by the use of high capacity Lithium rich layered materials. Apart from battery electrode, the thesis looks to develop activated carbon from a biodegradable source with low cost and low environmental impact. The biowaste material chosen in this thesis is human hair. Human hair was chosen because it is cheap to obtain and environmentally benign also the hair follicles are composed of loosely attached flakes which present a possibility of high surface area activated carbon. Dependence of the activation mechanism on the surface area and pore size distribution is studied. The final aim of this section is to develop a supercapacitor material with a high surface and optimum pore size distribution so that the energy stored in the capacitor electrode can be maximised. All the materials studied during the course of this thesis were carefully characterised to study structural morphological and electrochemical properties